Christianity and Schizophrenia Redux An Empirical Study - Kéri Szabolcs (JOURNAL OF RELIGION & HEALTH, 2020)
This paper explores the relationship among schizophrenia, spirituality, and Christian religiosity. We interviewed 120 patients with schizophrenia and 120 control individuals (74.2 % of individuals with self-reported Christian religions). Patients with schizophrenia showed increases in positive spirituality and decreases in positive congregational support, as measured by the Brief Multidimensional Measure of Religiousness/Spirituality. There was no significant difference in Christian religiosity. Higher positive spirituality was predicted by more severe self-disorder, perceptual disorder, and positive clinical symptoms. Schizophrenia patients with religious delusions did not exhibit enhanced Christian beliefs and rituals. These results do not confirm the hypothesis of general hyper-religiosity in schizophrenia.